Distribution and Correlation of Events During Thermal Inactivation of Bacillus megaterium Spores - Levinson, Hillel S. (1971)
Aqueous suspensions of Bacillus megaterium QM B1551 spores were heated at temperatures from 75 to 85 C. The rapid initial viability loss, followed by a more gradual, almost exponential decline, was not due to mixed populations with discrete heat resistances. The slight “tailing” below 0.01% survival was not the result of heat adaptation. Loss of viability was more rapid than loss of dipicolinic acid (DPA) and germinability and, although these events could not be correlated by use of simple kinetic plots, they had similar activation energies (80 to 90 kcal/mole). Probability (probit) plots of per cent survival as a function of logarithmic time yielded not the single line expected, if the heat resistances of individuals in the population were log-normally distributed, but two straight lines intersecting at a survival level of 1 to 6%. Probit-intersects occurred at times ranging from 8 min for spores heated at 85 C, to 310 min at 75 C. Probit-intersects for DPA release and loss in germinability occurred at the same time as for survival, but at much higher levels of retention. There appeared to be two subpopulations, both log-normally distributed but with different mechanisms of kill. Ninety-four to 99% of the spores died via injury to the cell-division process but retained germinability; the remaining smaller subpopulation (1 to 6%) was nonviable because of loss of the ability to germinate.